Criticism of Accountability in Social Forestry Partnership from Habermas Perspective - Ramadhan, Taufiq; Sukoharsono, Eko Ganis; Purwanti, Lilik (Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to reveal the reality of accountability of the LMDH Wono Lestari forestry partnership and criticize the practices that occur from Habermas' perspective. This research uses a qualitative method of critical paradigm case study. The research site is at LMDH Wono Lestari, Burno Village, Lumajang Regency. Informants consisted of representatives of the new LMDH management, old LMDH members, Perum Perhutani employees, agricultural commodity offtakers, and the community. Data analysis uses Jurgen Habermas' critical perspective. Accountability practices such as transparency and LMDH functions do not work. Likewise, there is low member participation, lack of management participation, and work plans that are not running well. The above causes internal and external conflicts for LMDH. It is necessary to update regulations and clarify the profit-sharing mechanism regarding the Forestry Partnership between LMDH Wono Lestari and Perum Perhutani in terms of accountability and transparency, such as the involvement of the Village Government as a partnership supervisor, as well as instilling honesty and expecting blessings from the Forestry Partnership.